Risk assessment of Diabetes using the Indian Diabetes Risk Score in an urban resettlement colony of East Delhi - Acharya, Anita Shankar; Debbarma, Shibajee; Rasania, Sanjeev Kumar; Tiwari, Nidhi; Bachani, Damodar; Khandekar, Jyoti (Indian Journal of Community Health, 2020)
Background- The burden of diabetes in India is expected to worsen in the coming years. Indian Diabetes Risk Score (IDRS) is a validated and cost?effective tool to identify risk of developing diabetes among population. Objectives- To assess the risk of Type 2 Diabetes mellitus using the IDRS in adults aged 30 years and above and to study the association of risk of diabetes with other factors. Material & Methods- A cross-sectional study was conducted in Kalyanpuri area of East Delhi. Data collection was done from August to December, 2018. 494 residents aged 30 years and above were included in the study. Data was collected using a semi-structured questionnaire. SPSS version 23 was used for data analysis. Results- 43.7 % of the study subjects were aged 50 years or above and majority (65.38%) were females. More than half (59.31%) of the subjects were found to have high risk of diabetes. Age and central obesity were found to be significantly associated with risk of diabetes (p<0.05). Risk of developing diabetes was not associated with gender. Conclusion- Early detection of risk of diabetes by periodic screening and appropriate behavioral change communication would be effective in controlling the diabetes crisis.